2022
DOI: 10.1002/ece3.8510
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conceptual framework for managing and conserving marine habitats: A case study of kelp forests in the Salish Sea

Abstract: Kelp forests are in decline across much of their range due to place‐specific combinations of local and global stressors. Declines in kelp abundance can lead to cascading losses of biodiversity and productivity with far‐reaching ecological and socioeconomic consequences. The Salish Sea is a hotspot of kelp diversity where many species of kelp provide critical habitat and food for commercially, ecologically, and culturally important fish and invertebrate species. However, like other regions, kelp forests in much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 207 publications
(230 reference statements)
0
8
0
Order By: Relevance
“…The effective management of kelp forest ecosystems will depend on our ability to understand and mitigate the stressors limiting their resilience and distributions (Hollarsmith et al, 2022); our data contribute critical insights in this regard. Our study illustrates how variation within even a relatively small region could lead to substantially different levels of resilience across local kelp forest habitats, and this should be considered when designing monitoring schemes or interpreting monitoring data.…”
Section: Discussionmentioning
confidence: 99%
“…The effective management of kelp forest ecosystems will depend on our ability to understand and mitigate the stressors limiting their resilience and distributions (Hollarsmith et al, 2022); our data contribute critical insights in this regard. Our study illustrates how variation within even a relatively small region could lead to substantially different levels of resilience across local kelp forest habitats, and this should be considered when designing monitoring schemes or interpreting monitoring data.…”
Section: Discussionmentioning
confidence: 99%
“…In a warming global ocean, it is critical to determine the thermal tolerance of foundation species such as bull kelp so that we can model the future effects of climate change on kelp forest ecosystems. Although we cannot lower seawater temperatures in the Salish Sea without significant efforts to mitigate climate change on a global scale, we can use this information to prioritize management and conservation actions (Hollarsmith et al, 2022). We observed that high nitrogen concentrations did not enhance the survival of microscopic stages of bull kelp that were exposed to elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence collected over the past two or more decades indicates that kelp forests are decreasing in abundance and extent across certain parts of the world due to combined effects of climate change and localized threats, including fishing, sewage run-off, invasive species and changes in freshwater outflow (Krumhansl et al, 2016; Filbee-Dexter & Wernberg, 2018; Wernberg et al, 2019; Hollarsmith et al, 2022). However, the trajectories of kelp forests around the world have been highly variable, with some regions showing stability (e.g., Chile and the Falkland Islands; Mora-Soto et al, 2021) or even increases in abundance (e.g., South Africa; Bolton et al, 2012), highlighting the importance of refugia at global, regional and local scales (Krumhansl et al, 2016; Wernberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Various abiotic and biotic factors may make kelp more resilient in the face of warming and shifts in trophic dynamics (Hollarsmith et al, 2022). Spatial variation in temperature and other environmental variables can mediate the responses of kelp forests to large-scale warming (Wernberg et al, 2016; Cavanaugh et al, 2019; Starko et al, 2019; Filbee-Dexter et al, 2020), with factors like water motion, upwelling dynamics, and nutrient pollution leading to complexity in the distribution of environmental variation across the coastal fringe (Druehl, 1978; Hollarsmith et al, 2022; Spiecker & Menge, 2022; Starko et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation